An investigation of photochromic behavior of 6-Nitro BIPS - Wahid, Zaharah; Nadir, Najiah (2013)
Among many types of photochromic molecules, spiropyran has gained much attention due to its promising potential commercial application. In order to thoroughly understand its photochromic behavior, it is crucial to determine the effect of the variables that influence the absorption and intensity of the wavelength before and after UV irradiation. Thus, this paper presents an experimental technique to investigate the influence of solvent polarity, duration of light exposure and dye concentration variables on 6-nitro-1’,3’,3’-trimethylspiro[2H-1-benzopyran-2,2’-indoline] (6-Nitro BIPS). Full factorial experimental design was employed in this study. Three variables at 2-level setting were used. The variables levels were fixed. Analysis of variance (ANOVA) was used in the analysis of the experimental results. This investigation also explores and evaluates the interaction between the concentration and solvent variables. The interaction between the wavelength and the intensity variables were also examined. Detailed investigation on the chemical mechanism of the reaction or behavior of the photo transformation of 6-Nitro BIPS will also be discussed